Seven-Year Follow-Up of Peutz-Jeghers Syndrome - Hamid Reza Mozaffari; Fetemeh Rezaei; Roohollah Sharifi; S. Ghasem Mirbahari (Hindawi Limited, 2016)
One of the clinicopathological criteria for diagnosing Peutz-Jeghers syndrome (PJS) is mucocutaneous pigmentation. We present a 57-year-old Iranian female patient with diffuse pigmentation in buccal and labial mucosa. The first colonoscopy revealed one 0.5 cm rectal polyp. However surveillance colonoscopies over a 7-year polyp showed over 100 colorectal polyps.